PENGGUNAAN ANIME (ANIMATION LEARNING MEDIA) DALAM PENINGKATAN PENGUASAAN KOSAKATA BAHASA ARAB SISWA KELAS XI MA MUHAMMADIYAH LIMBUNG GOWA - Alim, Khairun Muqtadira; Ulum, Fatkhul; Hasmawati, Hasmawati (Universitas Muhammadiyah Tapanuli Selatan, 2025)
This study is a Classroom Action Research (CAR) aimed at examining the planning, implementation, and results of improving students' Arabic vocabulary mastery using ANIME (Animation Learning Media). The subjects of the study were 17 students from class XI.A at MA Muhammadiyah Limbung. Data collection techniques used were observation and tests. The data analysis techniques employed were qualitative and quantitative analysis. The research was conducted over two cycles. The findings revealed effective collaboration between the researcher and the teacher during the planning phase of the lessons, as well as increased teacher and student activities during the implementation of the lessons in each meeting. Moreover, based on the final test results, the students' average scores improved from 77.12 in the first cycle to 90.29 in the second. This indicates an improvement in students' Arabic vocabulary mastery by 13.17 points. Therefore, it can be concluded that ANIME (Animation Learning Media) can enhance students' Arabic vocabulary mastery.